Contributions of persisters and the Eagle effect to survival of Yersinia pseudotuberculosis under clinical antimicrobials - Olivia Goode; Jilly Woodward; Urszula Łapińska; Sophia Zborowsky; Jemima Onime; Audrey Farbos; Paul O’Neill; Aaron Jeffries; Christopher H. Jenkins; Isobel H. Norville; Stefano Pagliara (Microbiology Spectrum, 2026)
ABSTRACT Microbes have evolved a variety of strategies to survive exposure to naturally occurring and synthetic antimicrobials. These strategies have been investigated extensively in model bacterial organisms, whereas less is known about under explored pathogenic bacteria such as bacteria within the Yersinia genus. In this study, we investigated the inhibitory effect and bactericidal activity of antibiotics from five different classes and of the disinfectant hydrogen peroxide against Yersinia pseudotuberculosis , the ancestral species from which Yersinia pestis and Yersinia enterocolitica have emerged. We found that Y. pseudotuberculosis is able to survive exposure to clinical antibiotics and disinfectants by employing a variety of strategies, with persisters and the Eagle effect playing a role in survival to quinolones, tolerance playing a role in survival to ceftriaxone and overexpression of catalases and peroxidases contributing to survival to hydrogen peroxide. Our findings suggest that future research should focus on informing new, effective ways to treat infections caused by Yersinia species. IMPORTANCE Antimicrobial resistance is a complex phenomenon that constitutes one of the top global public health threats. Besides encoding genes that confer heritable resistance to antibiotic treatments, bacterial populations can also transiently survive antibiotic treatment, a phenomenon known as tolerance, or contain subpopulations, named persisters, that survive treatment while the majority of the population is killed by antibiotic treatment. Here, we investigate resistance, tolerance, and persistence of the bacterial pathogen Yersinia pseudotuberculosis to clinically relevant antibiotics and disinfectants. We show that Y. pseudotuberculosis populations contain persisters that survive treatment to two potent classes of antibiotics, the fluoroquinolones and cephalosporins, and to the widely used disinfectant hydrogen peroxide. Counterintuitively, increasing the concentration of fluoroquinolones employed decreases their activity against Y. pseudotuberculosis , a paradoxical effect known as the Eagle effect.